Pediatric HIV in India: Current scenario and the way forward - Anita Nath (Wolters Kluwer Medknow Publications, 2017)
In India, the prevention of parent-to-child transmission and antiretroviral therapy services for HIV-infected mothers and children have been rapidly scaled up over the recent years. Despite these advances, a large number of HIV-infected children are born in every year. A thorough literature review has been done by retrieving related studies (published from the year 2000 onward); using a Medline search and by extracting recent findings from the official websites of the National AIDS Control Organization, UNAIDS, UNICEF, and World Health Organization. The efforts that are made to control pediatric HIV are challenged by a large range of factors such as low health service utilization, poor drug adherence, delayed infant diagnosis, discriminatory attitude of health providers, loss to follow-up, and poor coordination in managing continuum of care. These challenges may be addressed by adopting innovative and effective strategies and strengthening the existing health system. This would bring about a significant reduction in pediatric HIV incidence and improve the outcomes in children who are HIV infected.